General fractional financial models of awareness with Caputo–Fabrizio derivative - Amr MS Mahdy; Yasser Abd Elaziz Amer; Mohamed S Mohamed; Eslam Sobhy (Advances in Mechanical Engineering, 2020)
A Caputo–Fabrizio (CF) form a fractional-system mathematical model for the fractional financial models of awareness is suggested. The fundamental attributes of the model are explored. The existence and uniqueness of the suggest fractional financial models of awareness solutions are given through the fixed point hypothesis. The non-number request subordinate gives progressively adaptable and more profound data about the multifaceted nature of the elements of the proposed partial budgetary models of mindfulness model than the whole number request models set up previously. In order to confirm the theoretical results and numerical simulations studies with Caputo derivative are offered.